Physical activity of police officers: A systematic review Atividade física de policiais: Uma revisão sistemática - Bernardo V.M.* (2017)
© 2017, Editorial Ciencias Medicas. All rights reserved.Physical activity is an important aspect of human health, especially for people who depend on the body and mind for good performance of their professional functions, as is the case of the police. This study aimed to summarize the scientific literature on the physical activity of police officers through a systematic review. Medline, PubMed, CINAHL and SCOPUS databases were reviewed as well as articles identified through a manual search. The search strategy included descriptors related to physical activity and the police corps population, with no date or language restriction. The results showed there are incipient studies related to the physical activity of the police corps. However, there was an inadequate level of physical activity, as well as cardiovascular, orthopedic, social and emotional consequences related to this population.